Enfrentamento da pandemia de Covid-19 no município de Santa Maria - RS: análise a partir de Mário Testa - Seerig, Ana Paula (2021)
The health crisis triggered by the covid-19 pandemic required adaptations and changes in the assistance and management of the Brazilian Unified Health System (Sistema Único de Saúde - SUS) and tested the capacity of governments. This study – Professional Master’s Thesis in Health Sciences, CCS, UFSM – presents an analysis of the dispute over the conduct of SUS’s actions in the city of Santa Maria, RS. The aim was to analyze, based on Mario Testa’s Coherence Postulate, the subjects and institutions that interfered in the way of confronting the health crisis during the first year of the covid-19 pandemic. This study uses propositions from cartographic research, with records and analysis based on the main author’s experience. The period studied was divided into three moments, with the identification of theories and methods in their possible relationships with government purposes and with the role of the state. The research analyzes the repercussions of disputes in the production of care networks, in management styles and in the strengthening or weakening of local organizations. The results show that public institutions (UFSM, HUSM and the city’s health surveillance sector) based their interventions on concepts inscribed in the scientific paradigm and, by supporting the updated recommendations of international organizations, they assured the scope of the main measures taken by public authorities. Concomitantly, in the same public sector, groups of professionals in alliance with the private sector broke with the relationship between theory and method, promoting changes in the assessment of the severity of the disease and in the methods of transmission control. Actors associated with market medicine, at first, advocated for contradictory conducts, standing between the recognition of the severity and the release of measures that impacted the commerce in the city. The new connection between theory, method and government purpose occurs, for this group, in the advocacy of medication without scientific evidence. Despite the consensus identified in the public sector, at first, the intervention methodology was restricted to isolation activities and hospital care. Primary Health Care (PHC) was tardily activated, reflecting a national trend. It is concluded that the health crisis was confronted with different understandings of the severity of the disease, the transmission dynamics and the means of individual and collective protection. The consensus between the public institutions operating in the city and the SUS’s management at the state level was crucial for ensuring actions of prevention, research and assistance. Actors in the public sector sought legitimacy in internationally recognized institutions, whereas actors in the private sector sought to legitimize the methodology of intervention (or non-intervention) according to indications of the federal government. The case of Santa Maria confirms the coherence between the political perspective (view of the role of the state and government actions) and the choice of sanitation theories and intervention methods. It is also an institutional crisis, with a return to more centralized models, with the reaffirmation of the hospital as a place for treatment and the campaign as a model of organizing collective actions, especially vaccination. The analysis of the complexity of this moment provides cues for a more qualified involvement in the struggle for the SUS’s institutionality.